Undergraduate algebra in nineteenth-century Oxford. Issue 2 (4th May 2017) - Gage, Joseph
Abstract : The nineteenth century was an important period for both Oxford mathematics and algebra in general. While there is extensive documentation of mathematical research in Oxford at this time, the same cannot be said of the teaching. The content of the course presents a different picture: it shows what those who set it felt was most valuable for a young mathematician to learn, perhaps indicating what direction they expected mathematics to take in the future. To find out what undergraduates were taught, I have looked through examination papers of the years between 1828 and 1912 with a focus on algebra, as well as supporting material. In this paper I will present my findings. I will give a picture of what an Oxford undergraduate's course in algebra looked like by the end of the nineteenth century and discuss my own conclusions as to why it took such a form.